N-acetyl Cysteine Administration Is Associated With Increased Cerebral Glucose Metabolism in Patients With Multiple Sclerosis: An Exploratory Study - Monti, Daniel A.; Zabrecky, George; Leist, Thomas P.; Wintering, Nancy; Bazzan, Anthony J.; Zhan, Tingting; Newberg, Andrew B. (Frontiers in Neurology, 2020)
Background: Multiple Sclerosis (MS) is an autoimmune disease marked by progressive neurocognitive injury. Treatment options affording neuroprotective effects remain largely experimental. The purpose of this proof of concept study was to explore the effects of N-acetyl-cysteine (NAC) on cerebral glucose metabolism (CMRGlu) and symptoms in patients with multiple sclerosis (MS). Methods: Twenty-four patients with MS were randomized to either NAC plus standard of care, or standard of care only (waitlist control). The experimental group received NAC intravenously once per week and orally the other six days. Patients in both groups were evaluated at baseline and after 2 months (of receiving the NAC or waitlist control period) with an integrated Position Emission Tomography (PET)/ Magnetic Resonance Imaging (MRI) scanner, using 18F Fluorodeoxyglucose (FDG) to measure cerebral glucose metabolism. Following imaging evaluation at 2 months, subjects initially attributed to the standard of care arm were eligible for treatment with NAC. Clinical and symptom questionnaires were also completed initially and after 2 months. Results: The FDG PET data showed significantly increased cerebral glucose metabolism in several brain regions including the caudate, inferior frontal gyrus, lateral temporal gyrus, and middle temporal gyrus (p<0.05) in the MS group treated with NAC, as compared to the control group. Self-reported scores related to cognition and attention were also significantly improved in the NAC group as compared to the control group. Conclusions: The results of this study suggest that NAC positively affects cerebral glucose metabolism in MS patients, which is associated with qualitative, patient reported improvements in cognition and attention. Larger scale studies may help to determine the clinical impact of NAC on measures of functioning over the course of illness, as well as the most effective dosage and dosing regimen.